Community context of crime: a longitudinal examination of the effects of local institutions on neighborhood crime - Wo, James C. (Crime & delinquency, 2016)
Although theories posit that some types of local institutions will have a crime-producing influence in neighborhoods while others will have the opposite effect, the empirical evidence is far from conclusive. Previous studies are typically limited to analyzing cross-sectional data and one type of institution. Using longitudinal data of the number of employees of various institutions within census tracts across nine U.S. cities, the present study examines the longitudinal impact of four types of institutions on violent and property crime. Negative binomial regression models suggest that alcohol outlets and banking establishments increase criminal opportunities, whereas “third places” like coffee shops and cafes induce efficacious neighborhood control and social action. Civic and social organizations have no statistical relationship with crime.